(untitled) (Al-Farooq Journal of Sciences, 2026)
This research paper addresses the issue of illegal migration in Libya and its implications for public health and social cohesion. With the increasing spread of this phenomenon, concerns have grown regarding its negative effects on citizens’ health due to the possible transmission of infectious and dangerous diseases, in addition to its impact on social behaviors and cultural values. Illegal migration in Libya is a complex phenomenon influenced by economic, political, and security factors, and Libya has become both a transit and destination country for hundreds of thousands of migrants. Available studies indicate serious health consequences for citizens, as well as social and security challenges affecting Libyan society. The study of illegal migration and its impact on public health and social cohesion in Libya is considered an important topic that attracts significant attention from researchers and specialists in social affairs and public health. The paper highlights the importance of addressing this issue, as it threatens society on multiple levels, particularly health, social, and economic aspects. Furthermore, the uncontrolled entry of individuals without proper health protocols may contribute to the spread of diseases and epidemics, while the introduction of unfamiliar cultures and values may weaken the prevailing social value system.